Improvement of adventitious root formation in flax using hydrogen peroxide - Takáč, Tomáš; Obert, Bohuš; Rolčík, Jakub; Šamaj, Jozef (New biotechnology, 2016)
Flax (Linum usitatissimum L.) is an important crop for the production of oil and fiber. In vitro manipulations of flax are used for genetic improvement and breeding while improvements in adventitious root formation are important for biotechnological programs focused on regeneration and vegetative propagation of genetically valuable plant material. Additionally, flax hypocotyl segments possess outstanding morphogenetic capacity, thus providing a useful model for the investigation of flax developmental processes. Here, we investigated the crosstalk between hydrogen peroxide and auxin with respect to reprogramming flax hypocotyl cells for root morphogenetic development. Exogenous auxin induced the robust formation of adventitious roots from flax hypocotyl segments while the addition of hydrogen peroxide further enhanced this process. The levels of endogenous auxin (indole-3-acetic acid; IAA) were positively correlated with increased root formation in response to exogenous auxin (1-Naphthaleneacetic acid; NAA). Histochemical staining of the hypocotyl segments revealed that hydrogen peroxide and peroxidase, but not superoxide, were positively correlated with root formation. Measurements of antioxidant enzyme activities showed that endogenous levels of hydrogen peroxide were controlled by peroxidases during root formation from hypocotyl segments. In conclusion, hydrogen peroxide positively affected flax adventitious root formation by regulating the endogenous auxin levels. Consequently, this agent can be applied to increase flax regeneration capacity for biotechnological purposes such as improved plant rooting.
Keywords: Naphthaleneacetic Acids; len; hypokotyl; Antioxidants; kyseliny indoloctové; biotechnologie; Indoleacetic Acids; peroxid vodíku; regulátory růstu rostlin; Plant Roots; kyseliny naftalenoctové; Biotechnology; antioxidancia; kořeny rostlin; Flax; Cellular Reprogramming; Hypocotyl; přeprogramování buněk; Plant Growth Regulators; Hydrogen Peroxide